Penguatan Brand Image Sego Jajang Guna Membangun Reputasi Culinary Tourism Di Desa Gintangan - Hartini, Frida Sucila; Mecha, I Putu Sudhyana; Sanjaya, Aditya Wiralatief (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2021)
Gintangan Village is famous for its woven bamboo education tourism, but its culinary tourism is still not widely known. One of the local culinary can be used as a component of the reputation formation of culinary tourism in Gintangan Village is Sego Jajang. However, the lack of introduction of the Sego Jajang brand to the public has resulted in the lack of people knowing it. The purpose of this study was to determine the extent to which the image of Sego Jajang in the eyes of the local community, as well as the efforts that can be made to strengthen the brand image of Sego Jajang. This research method uses descriptive qualitative analysis techniques of reduction, display, and conclusion drawing (verification). The results of the research from 30 sample people showed 25% of the community called Sego Jajang and Tempe Godhong as the local culinary delights of Gintangan Village. 86% stated that they know the whereabouts of Sego Jajang. The whole local community stated that they did not know the history of Sego Jajang. The level of ignorance for materials, tools, and the process of making Sego Jajang is still high, while for information on where to buy it the majority knows. 87% stated that the role of the Gintangan Village Government was still not optimal. 42% stated that social media used was Facebook. Besides, 93% gave their future roles in the form of online and offline promotions. Based on the results of the research, it is necessary to implement a brand strategy to identify and overcome the shortcomings of the brand image of Sego Jajang. Keyword: Brand Image, Sego Jajang, Culinary Tourism.